Changes in weight and health behaviors after pregnancies complicated by gestational diabetes mellitus: The CARDIA study. (13th May 2013) - Bennett, Wendy L.; Liu, Su‐Hsun; Yeh, Hsin‐Chieh; Nicholson, Wanda K.; Gunderson, Erica P.; Lewis, Cora E.; Clark, Jeanne M.
Abstract : Objective: Prepregnancy to postpregnancy change in weight, body mass index (BMI), waist circumference, diet, and physical activity in women with and without gestational diabetes mellitus (GDM) were compared. Design and Methods: Using the Coronary Artery Risk Development in Young Adults study, women with at least one pregnancy during 20 years of follow‐up ( n = 1, 488 with 3, 125 pregnancies) was identified. Linear regression with generalized estimating equations to compare prepregnancy to postpregnancy changes in health behaviors and anthropometric measurements between 137 GDM pregnancies and 1, 637 non‐GDM pregnancies, adjusted for parity, age at delivery, outcome measure at the prepregnancy exam, race, education, mode of delivery, and interval between delivery and postpregnancy examination were used. Results: When compared with women without GDM in pregnancy, women with GDM had higher prepregnancy mean weight (158.3 vs. 149.6 lb, P = 0.011) and BMI (26.7 vs. 25.1 kg/m 2, P = 0.002), but nonsignificantly lower total daily caloric intake and similar levels of physical activity. Both GDM and non‐GDM groups had higher average postpartum weight of 7‐8 lbs and decreased physical activity on average 1.4 years after pregnancy. Conclusions: Both groups similarly increased total caloric intake but reduced fast food frequency. Prepregnancy to postpregnancy changes in body weight, BMI, waist circumference, physical activity, and diet did not differ between women with and without GDM in pregnancy. Following pregnancy, women with and without GDM increased caloric intake, BMI, and weight and decreased physical activity, but reduced their frequency of eating fast food. Given these trends, postpartum lifestyle interventions, particularly for women with GDM, are needed to reduce obesity and diabetes risk.